Rowing rib stress injury: What rowers and coaches need to know - Ruth, W. (Rowing Stronger, 2024)
Rib stress injuries are an overuse injury affecting up to approximately 10% of rowers in a given year of training. While not as common as other injuries, the long recovery time of a bone injury makes it the costliest injury in terms of total missed training time per injury. Injury risk increases with training volume: Collegiate and elite rowers doing more total training volume experience more rib stress injuries than masters and junior rowers. This article is a practical guide to what rowers and coaches need to know about rowing rib stress injuries, focusing on preventing, managing, and returning from injury to full performance.